1967
DOI: 10.1093/bja/39.8.633
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam (Valium) as a Muscle Relaxant During General Anaesthesia: A Pilot Study

Abstract: Diazepam (Valium) was given to 13 patients during nitrous oxide, oxygen and halothane anaesthesia. Abdominal relaxation was not regularly produced and the amount of tubocurarine required subsequently to produce relaxation was the same as required in patients who had not had diazepam. The drug produced central respiratory depression affecting tidal volume only. It tended to lower the blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1971
1971
1994
1994

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…The findings of the present study on the interaction of diazepam and d-tubocurarine in human beings are in conformity with those of Stovner and Endreson (19{) Hunter (1967) and Dretchen et al (1971). However, Stovner and Endreson (1965b), Moore (1968), Feldman and Crawley (1970a, 1970b and Yergano et al (HHO) found that diazepam potentiated the effect of small doses of specific neuromuscular blocking agents.…”
Section: Disccssiol\supporting
confidence: 91%
“…The findings of the present study on the interaction of diazepam and d-tubocurarine in human beings are in conformity with those of Stovner and Endreson (19{) Hunter (1967) and Dretchen et al (1971). However, Stovner and Endreson (1965b), Moore (1968), Feldman and Crawley (1970a, 1970b and Yergano et al (HHO) found that diazepam potentiated the effect of small doses of specific neuromuscular blocking agents.…”
Section: Disccssiol\supporting
confidence: 91%
“…Displacement of the carbon dioxide response lines appeared to be a better method of assessing our drugs. The respiratory depression caused by diazepam, when administered as an induction agent or during anaesthesia, has been well documented (McClish, 1966;Hunter, 1967). However, experimental studies, in man, on the effects of diazepam upon the ventilatory response to carbon dioxide has produced variable results.…”
Section: Animal Studiesmentioning
confidence: 99%
“…It is notable that the administration of respiratory depressant drugs to anaesthetized patients is associated with a greater degree of respiratory depression than would be predicted from their effect on PCO2 and ventilation in conscious volunteers (Potter and Payne, 1970). For example, in one study (Hunter, 1967) respiratory arrest occurred in three of 13 patients given diazepam 2.5-10mg during anaesthesia with nitrous oxide, oxygen and halothane, whereas the effect of diazepam 15mg on resting end-tidal PCO 2 in normal volunteers was to produce only a small increase of 0.2 kPa (Jordan, Lehane and Jones, 1980). Using magnetometers, Tusiewicz, Bryan and Froese, (1977) showed that halothane anaesthesia considerably diminished the rib cage contribution during quiet breathing, a finding supported by Jones and colleagues (1979) using mercury-insilastic strain gauges.…”
Section: Examples Of Effect Of Drugs On Resting Breathingmentioning
confidence: 99%